Poland in the Schengen Agreement – Opinion from the Borderland - Witkowski, Piotr (Regional Barometer. Analyses & Prognoses, 2009)
Poland accession to the Schengen Agreement removed systematic border control between Poland and other EU countries, but also caused more intensive control on the outer borders. Author thinks that this situation will cause consequences for close to border inhabitants trading on this areas. All observations in this article were based on surveys of Chelm citizens conducted by Zamosc University of Management and Administration. Two tendencies concerning natural persons were observed. First concerning Ukrainian inhabitants who were a source of cheaper excise duty goods carried and sold sometimes even with violation of law. Second tendency was related with official sole traders working in little regional areas.